Dynamics of Islamic College from an Educational Aspect - Ishak, Ishak; Ansori, M. Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to examine the dynamics of Islamic colleges from an education aspect that is developing in Indonesia. This work was written based on literary studies and in-depth understanding and accumulated understanding from various trusted primary book sources. This type of research is qualitative with a library research approach. Data collection techniques are carried out by collecting data. Sources of data come from books and journals. Data analysis technique using Content Analysis. This research results show that science development and technology in the globalization era have an impact on all dimensions of people's lives. This condition continues to roll in the dynamics of community life. Even PTKIN feels these developments impact. Therefore, PTKIN continues to make institutional and curriculum-updating efforts. Management of the College must be transparent and accountable so that all parties can access various information that exists and is being developed by universities. This needs to be considered by the manager of the university. This is because the campus has an academic climate. Of course, the entire academic community must think in a positive direction and have honesty and understanding, with leadership in College, where a leader must open a space that can be navigated and is not discriminatory to all campus residents.